Computational Biology - Fenyö, David (Methods in molecular biology, 2010)
Sequencing and Genome Assembly Using Next-Generation Technologies -- RNA Structure Prediction -- Normalization of Gene-Expression Microarray Data -- Prediction of Transmembrane Topology and Signal Peptide Given a Protein's Amino Acid Sequence -- Protein Structure Modeling -- Template-Based Protein Structure Modeling -- Automated Protein NMR Structure Determination in Solution -- Computational Tools in Protein Crystallography -- 3-D Structures of Macromolecules Using Single-Particle Analysis in EMAN -- Computational Design of Chimeric Protein Libraries for Directed Evolution -- Mass Spectrometric Protein Identification Using the Global Proteome Machine -- Unbiased Detection of Posttranslational Modifications Using Mass Spectrometry -- Protein Quantitation Using Mass Spectrometry -- Modeling Experimental Design for Proteomics -- A Functional Proteomic Study of the Trypanosoma brucei Nuclear Pore Complex: An Informatic Strategy -- Inference of Signal Transduction Networks from Double Causal Evidence -- Reverse Engineering Gene Regulatory Networks Related to Quorum Sensing in the Plant Pathogen Pectobacterium atrosepticum -- Parameter Inference and Model Selection in Signaling Pathway Models -- Genetic Algorithms and Their Application to In Silico Evolution of Genetic Regulatory Networks.